Targeting the cannabinoid CB2 receptor to attenuate the progression of motor deficits in LRRK2-transgenic mice. (August 2016) - Palomo-Garo, Cristina; Gómez-Gálvez, Yolanda; García, Concepción; Fernández-Ruiz, Javier
Graphical abstract: Abstract: Most of cases of Parkinson's disease (PD) have a sporadic origin, with their causes mostly unknown, although overexposure to some environmental factors has been found to occur in some cases. Other forms of parkinsonism are the consequence of dominant or recessive mutations in specific genes, e.g. α-synuclein, parkin and, more recently, leucine-rich repeat kinase 2 (LRRK2), whose G2019S mutation represents the most prevalent form of late-onset, autosomal dominant familial PD. A transgenic mouse model expressing the G2019S mutation of LRRK2 is already available and apparently may represent a valuable experimental model for investigating PD pathogenesis and novel treatments. We designed a long-term study with these animals aimed at: (i) elucidating the changes experienced by the endocannabinoid signaling system in the basal ganglia during the progression of the disease in these mice, paying emphasis in the CB2 receptor, which has emerged as a promising target in PD, and (ii) evaluating the potential of compounds selectively activating this CB2 receptor, as disease-modifying agents in these mice. Our results unequivocally demonstrate that LRRK2 transgenic mice develop motor impairment consisting of small anomalies in rotarod performance (presumably reflecting a deficit in motor coordination and dystonia) and a strong deficiency in the hanging-wire test (reflecting muscle weakness), rather than hypokinesia which was difficult to be demonstrated in the actimeter. These behavioral responses occurred in absence of any evidence of reactive gliosis and neuronal losses, as well as synaptic deterioration in the basal ganglia, except an apparent impairment in autophagy reflected by elevated LAMP-1 immunolabelling in the striatum and substantia nigra. Furthermore, there were no changes in the status of the CB2 receptor, as well as in other elements of the endocannabinoid signaling, in the basal ganglia, but, paradoxically, the selective activation of this receptor partially reversed the deficits in the hanging-wire test of LRRK2 transgenic mice. This was accompanied by normalization in LAMP-1 immunolabelling in the basal ganglia, although it is possible that other CNS structures, remaining to be identified, are involved in the behavioral improvement. In summary, our data support the interest of the CB2 receptor as a potential pharmacological target in LRRK2 transgenic mice, although the neuronal substrates underlying these benefits might be not completely related to the basal ganglia and to the presumed parkinsonian features of these mice.